Evaluación del contenido de Macamidas en tres ecotipos de Lepidium Meyenii (maca), cultivadas y secadas en la localidad de cerro de Pasco-Junín - Paredes Fuentes, Julitza (2015)
Lepidium meyenii (Maca) is a native resource of the central Andes of Peru that has achieved international importance due to its medicinal properties. The main active components presents in this plant are the macamides, secondary amides formed by benzylamine and a rest of fatty acid, with variable lengths of chain and degree of unsaturation. In the present work were identified and quantified by HPLC-DAD, N (3 metoxibenzyl)-tetradecanamide(1), Nbenzylhexadecanamide(2), N-(3-metoxibenzyl) hexadecanamide(3), N-benzyl-octadecanamide(5), N-benzyltetracosanamide(11); present in the pentanic extracts obtained by liquid-liquid continuous partition of methanolic extracts of yellow, black and red ecotypes. It was required a process of adaptation and standardization of the chromatographic analytical technique using a stationary C-18 and a mobile phase composed of acetonitrile and water acidified applied in gradient, at a temperature of 30° C and a flow of 0.5 mL/min., reaching a LOD and LOQ between 0.10 and 0.64 μg/mL and a percentage of recovery between 80.91% - 101.26%. Macamides found concentrations were in the range between 35.57 y 0.075 mg/g of dry maca. Being yellow ecotype that presented the highest amount of these macamides.